Primary desmoplastic small round cell tumor of the submandibular gland: a case report and literature review - Jiayu Zhou; Qingling Li; Baihua Luo; Xiaodan Fu; Chunlin Ou; Xiaomei Gao; Zhijie Xu; Deyun Feng; Keda Yang (BMC, 2022)
Abstract Background Desmoplastic small round cell tumor (DSRCT) is a sporadic, highly malignant tumor with a poor prognosis. The abdomen and pelvis have been reported as the primary localization sites. However, to the best of our knowledge, there are few reports on primary DSRCT in the submandibular gland. Case presentation We report a case of a 26-year-old Chinese man with a mass in the right submandibular gland. Imaging studies showed a hypoechoic mass in the right submandibular region. Intraoperative pathology revealed that the tumor tissue was composed of small round tumor cells and a dense desmoplastic stroma. On immunostaining, the tumor cells showed markers of epithelial, mesenchymal, myogenic, and neural differentiation. The EWSR1 gene rearrangement was detected by fluorescence in situ hybridization. Based on the overall morphological features and immunohistochemical findings, a final diagnosis of DSRCT was made. The patient was treated with comprehensive anti-tumor therapy mainly based on radiotherapy and chemotherapy. Conclusions DSRCT is an uncommon malignant neoplasm with rare submandibular gland involvement. In this report, we have described a case of DSRCT in the submandibular gland and reviewed the literature on DSRCT over the past 5 years. Considering the importance of differential diagnosis between DSRCT, especially with rare extra-peritoneal involvement, and small round blue cell tumors, a full recognition of the clinicopathological features will help to better diagnose this neoplasm.